(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aspergillus is a fungus and toxins produced by fungi that negatively affect patients’ lives, and recent research has focused on the relationship between different diseases caused by inhaling portions of fungi or fungal spores. There are some complete reports that fully reveal the relationship of Aspergillus fungi by determining the percentage of toxins produced by this type of fungi or their frequency in feed, food, or even clinical specimens, as well as the effect of toxins secreted by fungi on people who have been exposed to these fungi. It was purified from clinical samples, which included sputum, edema, wiping, tissue parts of the lung and other samples such as serum. As an immunological study, in addition to samples of cereals, nuts and homemade cheeses, as well as some other foods and vegetables. In this review, research in scientific research engines was conducted through four science-based data bases using the following keywords (Aspergillus fungi and the toxins they produce) (diseases associated with Aspergillus fungi). Scientific criteria were adopted in this review, and 41 subjects were selected. The results were compared in these articles regarding the presence of mushrooms in Iraqi governorates such as Najaf, Dhi Qar and Basra, as well as the frequency of mushrooms in Iraq and some neighboring countries such as Turkey, Saudi Arabia and Egypt. And Syria during the period 2009-2018 these results were compared with the WHO reports and the permissible proportions in food and feed. It was found that the highest rate of fungi was in Iraq at approximately 89.5%, while in Syria the frequency of fungi was 86.6% isolated, and in Egypt and Jordan it was 70.67% 77.6%, respectively, while in Saudi Arabia the Arabian Peninsula was 50.56% less frequent. The high rate of fungi frequency in Iraq may be due to black storage of foodstuffs, which has led to a high rate of fungi frequency and an increase in the proportion of foodstuffs or in clinical samples, according to the materials under study